2017
DOI: 10.1371/journal.pone.0170520
|View full text |Cite
|
Sign up to set email alerts
|

Differential Processing for Actively Ignored Pictures and Words

Abstract: Previous work suggests that, when attended, pictures may be processed more readily than words. The current study extends this research to assess potential differences in processing between these stimulus types when they are actively ignored. In a dual-task paradigm, facilitated recognition for previously ignored words was found provided that they appeared frequently with an attended target. When adapting the same paradigm here, previously unattended pictures were recognized at high rates regardless of how they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Mack and Rock (1998) found that participants could capture unattended natural scenes. One recent study suggested that pictures were processed more readily than words when attended; the reason might be because pictures could maintain more direct access to semantic representations compared to words, even under conditions in which pictures were actively ignored ( Walker et al, 2017 ). To our knowledge, there was no study that directly compared the IB rate for the unattended pictures and words; therefore, the present results need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mack and Rock (1998) found that participants could capture unattended natural scenes. One recent study suggested that pictures were processed more readily than words when attended; the reason might be because pictures could maintain more direct access to semantic representations compared to words, even under conditions in which pictures were actively ignored ( Walker et al, 2017 ). To our knowledge, there was no study that directly compared the IB rate for the unattended pictures and words; therefore, the present results need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because of the effects of similarity were inconsistent in previous studies, more evidences with differential experimental paradigm were warranted to further clarify the similarity on IB. Additionally, the pictures might be processed differently from the words ( Walker et al, 2017 ). Therefore, in the current study, we aimed to explore whether the similarity and attended stimuli (words or pictures) would influence the recognition accuracy of unattended stimuli with the dual-task experimental paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…If target detection facilitates context memory, then we might also expect to find a benefit for incidentally encoded background items. However, findings from previous studies have been mixed (e.g., Dewald et al, 2011, 2013; Swallow & Jiang, 2011, 2014; Walker et al, 2017).…”
Section: Context Memory In the Attentional Boost Effectmentioning
confidence: 90%
“…Studies in the United Kingdom show that students do not understand the purpose of learning history in school [24]. In this regard, it is important for the teacher or lecturer to provide an understanding of the purpose and benefits of learning about historical material at the beginning of the meeting so students understand well the positive things that are obtained by learning history.…”
Section: B Sports Disabilitymentioning
confidence: 99%